Failure costs associated with mastitis in smallholder dairy farms keeping Holstein Friesian × Zebu crossbreed cows - S.A. Mekonnen (Animal, 2019)
Mastitis is a costly disease and in many areas of the world, these costs have been quantified to support farmers in their decision making with regard to prevention of mastitis. Although for subsaharan circumstances estimates have been made for the costs of subclinical mastitis (SCM), farm-specific cost estimations comprising both clinical mastitis (CM) and SCM are lacking. In this paper, we quantified failure costs of both CM and SCM on 150 Ethiopian market-oriented dairy farms keeping Holstein Friesian × Zebu breed cows. Data about CM were collected by face-to-face interviews and the prevalence of SCM was estimated for each farm using the California mastitis test. All other relevant information needed to calculate the failure costs, such as the consequences of mastitis and price levels, was collected during the farm visits, except for the parameter for milk production losses due to SCM, which was based on literature estimates and subjected to sensitivity analyses. The average total failure costs of mastitis was estimated to be 4 765 Ethiopian Birr (ETB) (1 ETB = 0.0449 USD) per farm per year of which SCM contributed 54% of the costs. The average total failure costs per lactating cow per farm per year were 1 961 ETB, with a large variation between farms (range 0 to 35 084 ETB). This large variation in failure costs between farms was mainly driven by variation in incidence of CM and prevalence of SCM. Milk production losses made the largest contribution (80%), whereas culling contributed 13% to 17% to the total failure costs. In our estimates, costs of veterinary services, drugs, discarded milk and labour made a minor contribution to the total failure costs of mastitis. Relative to the income of dairy farmers in North Western Ethiopia; the total failure costs of mastitis are high. In general, Ethiopian farmers are aware of the negative consequences of CM, but creating awareness of the high costs of SCM and showing large variation between farmers may be instrumental in motivating farmers to also take preventive measures for SCM.